Phase-Field Simulation of the Creep Mechanism in the AZ31 Magnesium Alloy Under Discontinuous Dynamic Recrystallization Dominance - Alireza Rezvani; Ramin Ebrahimi; Ebad Bagherpour (Crystals)
Discontinuous dynamic recrystallization is a critical microstructural evolution mechanism during high-temperature deformation, influencing material properties significantly. This study develops a two-dimensional phase-field model to predict steady-state creep rates in the AZ31 magnesium alloy, focusing on DRX during creep. To enhance simulation accuracy, initial microstructures are generated from optical microscopy data, enabling simulations at larger scales with higher representativeness. A novel nucleation methodology is implemented, eliminating the need for nuclei order parameter adaptation, improving computational efficiency. Finite element analysis (FEA) is integrated to capture initial instantaneous deformation. The Kocks–Mecking model is employed to describe the evolution of average dislocation density, accounting for work hardening and dynamic recovery within the initial polycrystalline microstructure. Instead of conventional creep testing, impression creep, a cost-effective alternative, is used for validation. This method provides constant stress and steady penetration velocity, simulating creep conditions effectively. The model accurately predicts recrystallization kinetics and microstructural evolution, exhibiting a strong correlation with experimental results, with an error of approximately 5%. This research provides a robust and efficient approach for predicting creep behavior in high-temperature applications, vital for optimizing material selection and predicting component lifespan in industries. The methodology offers a significant advancement in understanding and predicting DRX-driven creep behavior.